The safety of treatments for tobacco use disorder. Issue 3 (3rd March 2016) - Little, Melissa A.; Ebbert, Jon O.
ABSTRACT: Introduction : Tobacco continues to be a leading cause of preventable morbidity and mortality in the world. First-line pharmacotherapies for the treatment of tobacco use disorder include nicotine replacement therapy, bupropion sustained-release (SR), and varenicline. We provide an overview of current evidence on the safety of first-line pharmacotherapies for the treatment of tobacco use disorder. Areas covered : Randomized clinical trials published in English up to July 2015 were identified and reviewed through searches of PUBMED using the terms nicotine replacement therapy, bupropion SR, varenicline, smoking, and tobacco cessation. Expert opinion : Nicotine replacement has few contraindications and side effects and can be recommended to almost all tobacco users. Bupropion SR should be used with caution in patients with bipolar disorder or liver or kidney disease, and alternative treatments should be considered for patients with a history of seizures or who are at risk for seizures. The only contraindication for varenicline is an allergy to the medication, and nausea is the most common side effect. Varenicline can be used safely in patients with cardiovascular disease. Varenicline can be used in patients with stable psychiatric disease and safety can be ensured through close clinical monitoring.